Synthesis, Structure and Antileishmanial Evaluation of Endoperoxide-Pyrazole Hybrids - Amado, Patrícia S M (2022)
Leishmaniases are among the most impacting neglected tropical diseases. In attempts to repurpose antimalarial drugs or candidates, it was found that selected 1,2,4-trioxanes, 1,2,4,5-tetraoxanes, and pyrazole-containing chemotypes demonstrated activity against Leishmania parasites. This study reports the synthesis and structure of trioxolane-pyrazole (OZ1, OZ2) and tetraoxane-pyrazole (T1, T2) hybrids obtained from the reaction of 3(5)-aminopyrazole with endoperoxide-containing building blocks. Interestingly, only the endocyclic amine of 3(5)-aminopyrazole was found to act as nucleophile for amide coupling. However, the fate of the reaction was influenced by prototropic tautomerism of the pyrazole heterocycle, yielding 3- and 5-aminopyrazole containing hybrids which were characterized by different techniques, including X-ray crystallography. The compounds were evaluated for in vitro antileishmanial activity against promastigotes of L. tropica and L. infantum, and for cytotoxicity against THP-1 cells. Selected compounds were also evaluated against intramacrophage amastigote forms of L. infantum. Trioxolane-pyrazole hybrids OZ1 and OZ2 exhibited some activity against Leishmania promastigotes, while tetraoxane-pyrazole hybrids proved inactive, most likely due to solubility issues. Eight salt forms, specifically tosylate, mesylate, and hydrochloride salts, were then prepared to improve the solubility of the corresponding peroxide hybrids and were uniformly tested. Biological evaluations in promastigotes showed that the compound OZ1•HCl was the most active against both strains of Leishmania. Such finding was corroborated by the results obtained in assessments of the L. infantum amastigote susceptibility. It is noteworthy that the salt forms of the endoperoxide-pyrazole hybrids displayed a broader spectrum of action, showing activity in both strains of Leishmania. Our preliminary biological findings encourage further optimization of peroxide-pyrazole hybrids to identify a promising antileishmanial lead.